TINGKAT MOTIVASI PETANI DALAM BETERNAK SAPI DI KECAMATAN SAMBAS KABUPATEN SAMBAS - Harmoko 2017 (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Farmers as cattle ranchers, the impetus for raising cows can provide benefits. In addition to the results from farming, cattle results can be used as a "treasure savings". The presumption treasure savings in rural communities in the form of livestock that can provide benefits when needed at the times when it was needed the money. The purpose of this study to determine the level of motivation of farmers to raise cattle and determine the factors that influence it. The research uses descriptive analytical method that aims to describe the motivation of farmers to raise cattle. Samples taken at random from a group of farmers in the villages in the subdistrict of Sambas. Analysis of data using multiple regression. The results showed that the level of motivation of farmers to raise cattle is very high. Factors that affect the motivation of farmers to raise cattle is attitude. In order for farmers positive attitude, do increase the capacity of farmers through workshops, seminar and workshops themed livestock.